2012
DOI: 10.1002/ejic.201101315
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Photoluminescence Quenching Relationships of Iridium(III)–Tris(phenylpyridine) Complexes

Abstract: Keywords: Iridium / Luminescence / Photoluminescence / Electrochemistry / Oxygen sensitivity / Density functional calculationsThe synthesis, structural, photophysical, theoretical, and electrochemical characterization of four tris(2-phenylpyridine)-based Ir III complexes are reported. The complexes were functionalized on the pyridine or on the phenyl rings with amide moieties substituted with a tris(ethyl)amine or ethyl groups, thereby yielding a family of compounds with hemicaged or open (without a capping un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…through triplet-triplet annihilation (TTA), spectral broadening and, in some cases, formation of precipitates. So far, several strategies have been used in order to favor cell internalization and prevent their quenching by dioxygen and water molecules, such as caged complexes, 21,104 encapsulation in polymeric matrices, linking polyethyleneglycol (PEG) moieties to the coordinated ligands, 105 increasing lipophilicity with long alkyl chains and bio-conjugation. 106,107 In particular, for platinum(II) complexes in either organic solvents or in the solid state, self-assembled structures lead to changes in properties which are interesting and could be used to improve their use as labels.…”
Section: Luminescent Pt(ii) Complexes As Bio-imaging Labelsmentioning
confidence: 99%
“…through triplet-triplet annihilation (TTA), spectral broadening and, in some cases, formation of precipitates. So far, several strategies have been used in order to favor cell internalization and prevent their quenching by dioxygen and water molecules, such as caged complexes, 21,104 encapsulation in polymeric matrices, linking polyethyleneglycol (PEG) moieties to the coordinated ligands, 105 increasing lipophilicity with long alkyl chains and bio-conjugation. 106,107 In particular, for platinum(II) complexes in either organic solvents or in the solid state, self-assembled structures lead to changes in properties which are interesting and could be used to improve their use as labels.…”
Section: Luminescent Pt(ii) Complexes As Bio-imaging Labelsmentioning
confidence: 99%
“…In this example the heterogenized catalyst operated via a monomeric mechanism, whereas in the homogeneous case a dimeric iridium complex that changed the mechanism was formed. It has also previously been reported that a heterogenized construct could prevent catalyst degradation pathways such as ligand dissociation/degradation. Thus, altogether, these points may explain why the heterogenized catalysts give a higher yield over time compared to the homogeneous ones.…”
Section: Resultsmentioning
confidence: 86%